Pengaruh Level Substitusi Rumput Suket Putihan (Bothriochloa pertusa) dengan Kangkung Ipomea reptans poir) Terhadap Pemanfaatan Energi Ternak Kambing Kacang - Wohangara, Yeremias Lu; Nenobais, Mariana; Benu, Imanuel (Animal Agricultura, 2024)
The aim of this experiment was to determine the effect of level substitution of Suket Putihan Grass (Bothriochloa pertusa) grass with water spinach (Ipomea Reptans Poir) on Energi Utilization of Kacang Goat. Four male kacang goats aged 1-1.5 years old with an initial body weight of 16,2 –19,8 kg (averaged ± 18 kg) were used in this study following a 4x4 Latin Square Design (RBSL) with 4 treatments and 4 periods as replications. The treatments were P0: 60% Bothriochloa pertusa + 40% lamtoro, P1:45% Bothriochloa pertusa + 40% lamtoro + 15% Ipomea Reptans Poir, P2 : 30% Bothriochloa pertusa + 40% Leucaena leucocephala + 30% Ipomea Reptans Poir, P3:15% Bothriochloa pertusa + 40% lamtoro + 45% Ipomea Reptans Poir. Parameters measured were energy consumption, energy digestibility, digestible energy and metabolisable energy. Data obtained were analyzed using the analysis of variance(ANOVA) The results showed that  substitution of Bothriochloa pertusa grass with Ipomea Reptans Poir had no significant effect (P>0,05) on all measured parameters. The conclusion is that the substitution of Suket Putihan grass (Bothriochloa pertusa) with water spinach (Ipomea Reptans Poir) does not affect Energy Utilization of kacang goats.